(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Captures of aphids (alatae viviparae) ha ve been made into maize cultures in 30 sites of Northern Italy with water-traps. A list ofthe collected species is given. Besides maize-aphids, severa! species ofthe surrounding flora were found.